Religion and Violence : Muslim and Christian Theological and Pedagogical Reflections - Aslan, Ednan; Hermansen, Marcia K. (Germany, Springer VS, Wiesbaden, 2017)
In this volume, the authors attempt to speak freely about the potential in religions both for violence and peace. I am confident that many impulses from this work will also impact the direction of churches and other religious communities, such that religions, all together, will try to mobilize the members of their communities to actively contribute to world peace. In this way, religions will be perceived as part of the solution for world peace, enabling them to move beyond the stigma of their damaged reputations. Content Religion and Violence - Islam and Violence - Religious Education and the Challenge of Violence The Editors Ednan Aslan is the Chair of Islamic Theological studies at the University of Vienna where he is a Professor for Islamic Education. Marcia Hermansen is Director of Islamic World Studies at Loyola University Chicago where she is a Professor in the Theology Department. > .
Religion and Violence -- Islam and Violence -- Religious Education and the Challenge of Violence.
Keywords: Crime; Culture; Emigration and immigration; Religion and sociology; Violence; Sociology of Religion; Migration; Religion and Society; Sociology of Culture; Violence and Crime